Linguistic Analysis of Insta, Twit Posts and LJ Blogs in the Context of Their Functions (Based on the Russian Language) - Novikova, Olga; Kalugina, Yuliya; Mustafina, Albina; Edeleva, Irina (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The present article is concerned with identifying the linguistic and extralinguistic features of Instagram, Twitter, and Live Journal hypertexts, depending on their functional focus. The relevance of the topic is due to the need for a more detailed study of Internet communication from the point of view of functional and stylistic aspects. The study provides a comparative analysis of Instagram, Twitter, and Live Journal online services based on the Russian language material. The results are correlated with the questionnaire data on the studied problem. The article discusses graphic, lexical, stylistic, syntactic, and spelling features. The authors conducted a comparative analysis of the hypertexts of Instagram, Twitter, and Live Journal online services in the context of their functions; identified linguistic and extralinguistic features of the hypertext of the services under study; established the relationship between the language of the text and the function implemented. It has been established that all three online services perform, first of all, a communicative function, which is expressed through the use of slang, vernacular, online discourse vocabulary, graphic means, markers of increased emotionality, recreation of a specific accent/dialect, spelling and punctuation violations, incomplete, unextended sentences. Along with the socialization function, Instagram performs the function of self-presentation, for the implementation of which the authors of publications resort to linguistic creativity. Unlike Instagram, Twitter, and Live Journal fulfill a more political function, expressed in stylistic devices such as metaphor, comparison, irony, hyperbole, and repetition. The results were verified using a questionnaire survey conducted among Russian students.